2022
DOI: 10.1097/jcma.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic head sparing surgery for solid pseudopapillary tumor in patients with agenesis of the dorsal pancreas

Abstract: Background: This study aimed to clarify the feasibility and justification of pancreatic head sparing (PHS) enucleation for patients with agenesis of the dorsal pancreas (ADP) associated with a solid pseudopapillary tumor (SPT). Methods: Data of the SPT patients with and without ADP, including clinical presentations, surgical options, and surgical and survival outcomes, were recruited for comparison. Results: A total of 31 patients with SPTs were included, three of whom displayed ADP and underwent PHS enucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…6 All contribute to the re-consideration of the old proverb “to do more and to lose more.” 7 The recent publication in the October issue of the Journal of the Chinese Medical Association entitled “Pancreatic head sparing surgery for solid pseudopapillary tumor in patients with agenesis of the dorsal pancreas,” showed the feasibility and possible safety of using sparing surgery of the pancreatic head (pancreatic head sparing surgery [PHSS]) in the management of patients with agenesis of the dorsal pancreas (ADP) accompanied by a solid pseudopapillary tumor (SPT). 8…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…6 All contribute to the re-consideration of the old proverb “to do more and to lose more.” 7 The recent publication in the October issue of the Journal of the Chinese Medical Association entitled “Pancreatic head sparing surgery for solid pseudopapillary tumor in patients with agenesis of the dorsal pancreas,” showed the feasibility and possible safety of using sparing surgery of the pancreatic head (pancreatic head sparing surgery [PHSS]) in the management of patients with agenesis of the dorsal pancreas (ADP) accompanied by a solid pseudopapillary tumor (SPT). 8…”
mentioning
confidence: 99%
“…8 The authors retrospectively enrolled three patients with ADP accompanied with SPT who were treated with PHSS, and the results showed all patients who were alive ranged from 22 months to 75 months, even though one patient could not be totally resected for her SPT. 8 Additionally, the authors evaluated 28 patients with SPT without ADP, and the outcomes of these patients were also excellent with a 100% of 20-year overall survival (OS) rate. 8 Then, based on the concept of preservation of pancreas function and/or avoidance of pancreatic insufficiency, the authors suggested that PHSS for SPT is a feasible and safe method, and they particularly emphasized its feasibility for SPT patients concomitant with ADP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 Life-saving is the most critical issue for cancer treatment; however, the patients not only wish to be cured from the diseases but also want to have a good to excellent posttreatment recovery as well as had better have their organ-preservation or complete return of the function to maintain good quality of life (QoL) in their remaining life, and these wishes now have become an optimal therapeutic goal for both physicians and patients. [2][3][4] An accurate and precise pretherapy evaluation and an appropriate and personalized therapeutic plan for these cancer or critically ill patients through the far-advanced development of new technology or therapeutic strategy, such as a minimally traumatic organ-preservation approach and a method for maintenance of physiological and morphological function of targeted lesions can minimize the risk of overtreatment and subsequently avoid the development of severe posttherapy sequelae without compromising the therapeutic efficacy. [5][6][7] To reach this goal, it is still challengeable.…”
mentioning
confidence: 99%